Solution;
Rewrite the equation as follows;
"y^2dy=(x^2dy-xydx)e^{\\frac xy}"
"y^2dy=x^2e^{\\frac xy}dy-xye^{\\frac xy}dx"
Combine as follows;
"xye^{\\frac xy}dx=(x^2e^{\\frac xy}-y^2)dy" ...(a)
1.)
From the above equation (a),
"M(x,y)=xye^{\\frac xy}dx"
The degree of M(x,y) is 1.
2.)
From the above equation (a);
"N(x,y)=x^2e^{\\frac xy}-y^2"
The degree of N(x,y) is 2.
3.)
Because of "e^{\\frac xy}" ,take "\\frac{dx}{dy}" instead of "\\frac{dy}{dx}"
From equation (a);
We obtain;
"\\frac{dx}{dy}=\\frac{x^2e^{\\frac xy}-y^2}{xye^{\\frac xy}}"
Now put ,F(x,y)="\\frac{dx}{dy}" and find "F(\\lambda x,\\lambda y)"
Hence we have ;
"F(\\lambda x,\\lambda y)=\\frac {(\\lambda x)^2e^{\\frac{\\lambda x}{\\lambda y}}-(\\lambda y)^2}{(\\lambda x)(\\lambda y)e^{\\frac{\\lambda x}{\\lambda y}}}"
"F(\\lambda x,\\lambda y)=\\frac{(\\lambda )^2[x^2e^{\\frac xy}-y^2]}{\\lambda^2xye^{\\frac xy}}" =F(x,y)
Clearly;
"F(\\lambda x,\\lambda y)=F(x,y)=\\lambda ^0F(x,y)"
Therefore ,the given equation is a homogeneous function of degree zero(0).
Comments
Leave a comment